Allometry Between Vegetative and Reproductive Traits in Orchids - Feng, Jing-Qiu; Zhang, Feng-Ping; Huang, Jia-Lin; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2021)
In flowering plants, inflorescence characteristics influence both seed set and pollen contribution, while inflorescence and peduncle size can be correlated with biomass allocation to reproductive organs. Peduncles also play a role in water and nutrient supply of flowers, and mechanical support. However, it is currently unclear whether inflorescence size is correlated with peduncle size. Here, we tested whether orchids with large diameter peduncles bear more and larger flowers than those with smaller peduncles by analysing 10 traits of inflorescence, flower and leaf in 26 species. Peduncle diameters were positively correlated with inflorescence length and total floral area, indicating that species with larger peduncles tended to have larger inflorescences and larger flowers. We also found strongly positive correlation between inflorescence length and leaf area, and between total floral area and total leaf area, which suggested that reproductive organs may be allometrically coordinated with vegetative organs. However, neither flower number nor floral dry mass per unit area were correlated with leaf number or leaf dry mass per unit area, implying that the function between leaf and flower was uncoupled. Our findings provided a new insight for understanding the evolution of orchids, and for horticulturalists interested in improving floral and inflorescence traits in orchids.